Antidepressant-Like Activity of Myelophil via Attenuation of Microglial-Mediated Neuroinflammation in Mice Undergoing Unpredictable Chronic Mild Stress - Lee, Jin-Seok; Kim, Won-Young; Jeon, Yoo-Jin; Lee, Sung-Bae; Lee, Dong-Soo; Son, Chang-Gue (Frontiers in Pharmacology, 2019)
Myelophil, a 30% ethanol extract that has an equal rate in both Astragali Radix and Salviae Radix, is a remedy for the treatment of fatigue-linked disorders in traditional Oriental medicine. The majority of patients with chronic fatigue have a risk of comorbidity with depression symptoms. To evaluate the anti-depressant activity of Myelophil, mice were subjected to unpredictable chronic mild stress (UCMS, eight different stresses) for 3 weeks with daily administration of distilled water, Myelophil (25, 50, or 100 mg/kg) or n-acetyl-l-cysteine (100 mg/kg). After the final stress exposure, three behavioral tests, including the open field test (OFT), forced swimming test (FST) and tail suspension test (TST), and stress-derived alterations of the serotonergic signal and inflammatory response in the hippocampus were measured. UCMS notably induced depressive behaviors, whereas these behavioral alterations were significantly reversed by the administration of Myelophil in regard to the OFT, FST, and TST results. Myelophil also significantly attenuated the over-activation of microglial cells and the inflammatory response in the hippocampal region (TNF-α, Tumor necrosis factor-alpha; IL-1β, Interleukin-1beta; and Caspase-1). Furthermore, Myelophil significantly restored the distortions of serotonergic function in the dorsal raphe nuclei and neurogenesis in the subgranular zone of the hippocampus. These results support the clinical relevance of the anti-depressant activity of Myelophil, specifically by modulating serotonergic function and the neuroinflammatory response.